REFLEKSI DIRI TERHADAP HUBUNGAN MANUSIA DAN ALAM SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI RUPA EKSPERIMENTAL - Sugiharto, Farid Dwi Bagus; Isnanta, Satriana Didiek (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2018)
Creation of experimental art with the title "Self Reflection Against Human and Natural Relations" in the background of the writer's anxiety about the environmental damage caused by humans. From the source of the idea, the writer creates experimental fine arts that will be used as an awareness media on how important the role of nature is for the survival of living thing on earth.The results of this creation are experimental installation with elements of painting, audio, video and motion installation to point a space. The processing of this final project refers to the method of creation of Henri Cholis which refers to Hawkins, namely that in the process of create there are three stages: exploration, imvising and forming.Â Keywords: self-reflection, experimental art, nature damageÂ